HNRNPA2B1, as a m6A Reader, Promotes Tumorigenesis and Metastasis of Oral Squamous Cell Carcinoma - Zhu, Feiya; Yang, Tianru; Yao, Mianfeng; Shen, Ting; Fang, Changyun (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A) modification is the most prevalent modification on eukaryotic RNA, and the m6A modification regulators were involved in the progression of various cancers. However, the functions of m6A regulators in oral squamous cell carcinoma (OSCC) remain poorly understood. In this study, we demonstrated that 13 of 19 m6A-related genes in OSCC tissues are dysregulated, and HNRNPA2B1 was the most prognostically important locus of the 19 m6A regulatory genes in OSCC. Moreover, HNRNPA2B1 expression is elevated in OSCC, and high level of HNRNPA2B1 is significantly associated with poor overall survival in OSCC patients. Functional studies, combining with further analysis of correlation between the expression of HNRNPA2B1 and the EMT-related markers from the TCGA database, reveal that silencing HNRNPA2B1 suppresses the proliferation, migration and invasion of OSCC via EMT. Collectively, our work shows that HNRNPA2B1 may have the potential to promote carcinogenesis of OSCC by targeting EMT via the LINE-1/TGF-β1/Smad2/Slug signaling pathway，and provides insight into critical roles of HNRNPA2B1 in OSCC.